Mengungkap Nilai Kearifan Lokal di Balik Praktik Akuntansi Pendapatan - Thalib, Mohamad Anwar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research departs from problems regarding adopting and implementing modern accounting, which impacts the increasingly marginalized accounting based on local cultural values. This study aims to construct income accounting practices based on local cultural values. The paradigm used in this research is Islam, with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The study results show that the bendi drivers earn a higher income when a flood occurs. Even so, they still feel empathy for the disaster experienced by residents and hope that the disaster will not be repeated. The income accounting practice is conditional on the value of empathy. In Gorontalo's Islamic culture, the elders often advise this value through lumadu “momoli’a layahu to dutalaa da’a” which means turning sails in a big storm. The meaning is taking opportunities when times are tight; this is dishonorable. The implication of the results of this research is to produce an accounting concept for income by bendi coachmen that are conditional onlocal cultural values.